Development of Problem-Based Learning Devices to Improve Critical Thinking Skills - Alfiani Syarifatul Ajri; Riki Perdana (Jurnal Inovasi Pendidikan dan Sains, 2023)
Learning tools can help teachers in a directed learning process. This study aims to produce problem-based learning physics learning tools to improve student's critical thinking skills that are appropriate for work and energy materials. This type of research is Research and Development (R&D) with a 4D development model consisting of four stages, namely Define, Design, Develop, and Disseminate. The learning tools developed are in the form of Learning Implementation Plans (RPP), Student Worksheets (LKPD), and learning outcomes assessment instruments in the form of multiple choices. The tool used in the development stage is a validation sheet. Learning device validation was carried out by expert lecturers and three students. The results of filling out the validation sheet were analyzed to calculate the percentage and then categorized in the cumulative score range. The research results obtained through the feasibility test of lesson plans, worksheets, and learning outcomes assessment instruments show that the development of problem-based learning tools has a very feasible category with a score above 80%. Based on these results, problem-based learning physics learning tools to improve critical thinking skills are appropriate for use in the learning process.